Characterizing the Microbiome of the Contracted Breast Capsule Using Next Generation Sequencing. (15th April 2020) - Cook, Jonathan; Holmes, Casey J; Wixtrom, Roger; Newman, Martin I; Pozner, Jason N
Abstract: Background: Recent work suggests that bacterial biofilms play a role in capsular contracture (CC). However, traditional culture techniques provide only a limited understanding of the bacterial communities present within the contracted breast. Next generation sequencing (NGS) represents an evolution of polymerase chain reaction technology that can sequence all DNA present in a given sample. Objectives: The aim of this study was to utilize NGS to characterize the bacterial microbiome of the capsule in patients with CC following cosmetic breast augmentation. Methods: We evaluated 32 consecutive patients with Baker grade III or IV CC following augmentation mammoplasty. Specimens were obtained from all contracted breasts (n = 53) during capsulectomy. Tissue specimens from contracted capsules as well as intraoperative swabs of the breast capsule and implant surfaces were obtained. Samples were sent to MicroGenDX Laboratories (Lubbock, TX) for NGS. Results: Specimens collected from 18 of 32 patients (56%) revealed the presence of microbial DNA. The total number of positive samples was 22 of 53 (42%). Sequencing identified a total of 120 unique bacterial species and 6 unique fungal species. Specimens with microbial DNA yielded a mean [standard deviation] of 8.27 [4.8] microbial species per patient. The most frequently isolated species were Escherichia coli (25% of all isolates), Diaphorobacter nitroreducens (12%), Cutibacterium acnes (12%), Staphylococcus epidermidis (11%), fungal species (7%), and Staphylococcus aureus (6%). Conclusions: NGS enables characterization of the bacterial ecosystem surrounding breast implants in unprecedented detail. This is a critical step towards understanding the role this microbiome plays in the development of CC. Level of Evidence: 4: